2014
DOI: 10.1111/ane.12308
|View full text |Cite
|
Sign up to set email alerts
|

Polyautoimmunity in a Greek cohort of multiple sclerosis

Abstract: Polyautoimmunity and particularly MAS occur more frequently in MS patients than in control participants indicating that MS may be part of a generalized susceptibility to autoimmunity. Therefore, polyautoimmunity may be implicated in the etiopathogenesis of MS-related ADs, with a potential impact on relative therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…After removing duplicates, our systematic search identified 285 studies. Ultimately, a total of six case-control studies with 12,930 study subjects that investigated the association of MS with vitiligo met our inclusion criteria [18][19][20][21][22][23] . We found no relevant cross-sectional or cohort studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After removing duplicates, our systematic search identified 285 studies. Ultimately, a total of six case-control studies with 12,930 study subjects that investigated the association of MS with vitiligo met our inclusion criteria [18][19][20][21][22][23] . We found no relevant cross-sectional or cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…In the Seyfert 1990 study, there were no cases of MS with vitiligo 19 ; therefore, we could not calculate the OR. Only one study 18 reported a positive association of MS with prevalent vitiligo. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Последние встречаются при РС с такой же частотой, как и в об-щей популяции, а иногда и реже [5,12]. Для пони-мания данного феномена большое значение приоб-ретают генетические исследования, в частности из-учение однонуклеотидных полиморфизмов (ОНП).…”
Section: распространенность и структура коморбидных аиз у больных рс unclassified